The Use of Textile-Based Materials in Shell System Design in Architecture and an Evaluation in Terms of Sustainability - TUGBA ALIOGLU; AYSE SIREL (Alanya Hamdullah Emin Paşa Üniversitesi, 2018)
The textile that has emerged from dressing and protection need of people against the variable weather conditions since the primaeval ages, has gained performance characteristics with the rise of artificial fibres apart from natural fibre production and with increasing technology and has gained a good position in architectural applications. The application areas of the textile, that was traditionally used as gear, as an indoor element, and as upholstery on furniture, have been varied by emerge of smart and technical textile and its use in construction sector and architecture has been actualized. The main textile-based materials used on building and skin systems are Polyvinyl Chloride (PVC), Polytetrafluoroethylene (PTFE), and Ethylene Tetra Fluoro Ethylene (ETFE). Tent, pneumatic building, canopy, pleated roof, umbrella, parasol, outer curtain, shear wall and façade are structural use forms of textile materials. While the interactions between textile and architecture actualized in a visual sense, structure and for technology, and aesthetic sense, the use of textile with its sustainability in architecture also brings advantages. In the paper, Eden Project, Water cube, and Alliance Arena where textile-based materials are used are studied. It is seen that the textile material, which is easily applied at long-spans and at forms which cannot be handled with traditional materials, became prominent with its recycling and sustainable features.